Greenhouse gases (CO2 and CH4) at an urban background site in Athens, Greece: Levels, sources and impact of atmospheric circulation. (15th May 2021) - Dimitriou, K.; Bougiatioti, A.; Ramonet, M.; Pierros, F.; Michalopoulos, P.; Liakakou, E.; Solomos, S.; Quehe, P.-Y.; Delmotte, M.; Gerasopoulos, E.; Kanakidou, M.; Mihalopoulos, N.
Abstract: Year-round carbon dioxide (CO2 ) and methane (CH4 ) concentration measurements, performed for the first time in the city of Athens, Greece from December 21, 2018 to December 31, 2019, are presented in this study and analyzed in relation to atmospheric circulation patterns at a local, regional and long-range transport scale. Clear diurnal and seasonal variations of both greenhouse gases were detected. The observed increased levels during night and early morning hours are attributed to traffic/heating emissions and leakages of residential natural gas for CO2 and CH4, respectively. Using CO2 and CH4 levels simultaneously measured at the regional background site at Finokalia (Greece), increments in their levels due to local and regional anthropogenic sources within the city were assessed. For CO2, maximum and minimum increments were clearly observed during winter and summer respectively, suggesting a greater impact of combustion of fossil fuel and especially of biomass on CO2 levels during winter. On the other hand, CH4 increments were similar in all seasons, suggesting that local sources of CH4 remain quite constant year-round. Through the implementation of the Conditional Probability Function (CPF), the emission sources of theses greenhouse gases have been localized to the northern and the eastern domains of the Athens basin. Stagnant atmospheric conditions were also associated with an increased likelihood of CO2 and CH4 episodes. Backward modeling simulations with FLEXPART and HYSPLIT models indicate an industrial zone and a petrochemical zone, situated to the north and to the west of Athens respectively, as possible CH4 regional sources as well as possible CO2 contributions from southern directions attributed to shipping emissions from the port of Piraeus. The present study provides knowledge needed for the determination of greenhouse gas emission mitigation strategies in Athens. Graphical abstract: Image 1 Highlights: Clear diurnal variability for both GHGs. Enhanced CO2 levels during winter nighttime due to combustion processes. Local CH4 sources remain quite constant throughout the year. Additional anthropogenic burden from urban CO2 emissions during winter around 6%. Regional CH4 sources from industrial/petrochemical zones enhancing levels.